Breast Tissue Biology Expands the Possibilities for Prevention of Age-Related Breast Cancers - Fresques, Tara; Zirbes, Arrianna; Shalabi, Sundus; Samson, Susan; Preto, Sandy; Stampfer, Martha R.; LaBarge, Mark A. (Frontiers in Cell and Developmental Biology, 2019)
Preventing breast cancer before it is able to form is an ideal way to stop breast cancer. However, there are limited existing options for prevention of breast cancer. Changes in the breast tissue resulting from the aging process contribute to breast cancer susceptibility and progression and may therefore provide promising targets for prevention. Here we describe new potential targets, immortalization and inflammaging, that may be useful for prevention of age-related breast cancers. We also summarize existing studies of warfarin and metformin, current drugs used for non-cancerous diseases, that also may be repurposed for breast cancer prevention.